Aggravation of cyclophosphamide-induced reproductive toxicity in mice by aqueous extract of Aegle marmelos (L.) - Sangita Singh; Awadhesh Kumar Mishra; Swarn Lata; Kavindra Nath Tiwari (Brazilian Journal of Pharmaceutical Sciences, 2017)
ABSTRACT Aegle marmelos (L.) (Rutaceae) commonly known as bael is an important medicinal fruit tree. The present study focused on the effects of aqueous extract of Aegle marmelos (AEAM) on the testis and sperm characteristics induced by cyclophosphamide (CPA) in mice. Thirty six adult Parke’s strain mice were divided into six groups: group I given only distilled water (control); group II administered with AEAM alone once in a week for five weeks; group III administered with CPA (200 mg/kg b.w., intraperitoneally) once in a week for five weeks and group IV-VI CPA along with AEAM (400, 500 and 600 mg/kg b.w., orally). CPA was found to reduce gonadosomatic index (GSI), sperm counts, motility, viability, antioxidant activities and induced histopathological changes of testis. In the group administered AEAM with CPA an exacerbation of sperm count, motility and viability of the cauda epididymis, GSI, antioxidant activities and architecture of testis was observed. The results suggest that the administration of AEAM may aggravate CPA-induced reproductive toxicity. It may be helpful in preparation of natural male contraceptives.